2017
DOI: 10.46743/2160-3715/2017.2211
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Marital Expectations in African Immigrant and United States-Born Married Couples

Abstract: The current phenomenological qualitative study aimed to understand marital expectations in married African immigrants and United States-born (U.S.-born) married couples. Eighty-five African-born immigrant and U.S.-born couples from a predominately Seventh-day Adventist sample residing in the U.S. completed the Marital Expectations Questionnaire (MEQ). We analyzed data collected in response to the first question. Data analysis revealed 12 codes associated with four themes related to marital expectations: (a) Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…The affective life as a couple is reportedly one of the dimensions of social life in which the greatest cultural maintenance seems to exist. In this case, the persistence of marked differences between groups does not coincide with studies in the US that show high cultural accommodation, assimilation and hybridisation in immigrant couples (Ngazimbi et al, 2017).…”
Section: Couple Relationships In the Immigrant Populationcontrasting
confidence: 68%
“…The affective life as a couple is reportedly one of the dimensions of social life in which the greatest cultural maintenance seems to exist. In this case, the persistence of marked differences between groups does not coincide with studies in the US that show high cultural accommodation, assimilation and hybridisation in immigrant couples (Ngazimbi et al, 2017).…”
Section: Couple Relationships In the Immigrant Populationcontrasting
confidence: 68%
“…One weakness concerns the models' theoretical nature (see Table 1) because they have been developed without prior empirical investigation. Additionally, these models do not fit in with other forms of the family organization resulting from demographic developments (e.g., increased age at first marriage and entry into parenting; increased divorce rate; and decreased fertility), and from ethnic and cultural variations (Carter & McGoldrick, 1995;Ngazimbi et al, 2017;Shange, 2010;Simões & Alberto, 2015Widmer & Gauthier, 2013). It is essential that the family evolutionary cycle models are adjusted to the cultural context of which the family system is a part.…”
Section: Systemic Models Of the Family Life Cyclementioning
confidence: 99%
“…Levels of total serum cholesterol and HDL (high-density lipoprotein) cholesterol were higher among AAs compared to BIs (Lancaster et al, 2006). A study of 214 Black men (138 BIs and 76 AAs) also showed that compared with AAs, waist circumference was lower among BIs; however, blood pressure and fasting glucose levels were higher among BIs (O'Connor et al, 2014). While health behaviors such as poor diet account for some of the disparities between BIs and AAs, factors in the environment such as family history, quality of neighborhoods, and exposure to stress may contribute to differences in health outcomes.…”
mentioning
confidence: 95%
“…Most BIs come from patriarchal cultures where deference to the husband is upheld. BIs also espouse the idea that marriage is an important milestone that improves social status (Ngazimbi, Daire, Carlson, & Munyon, 2017). These cultural views influence attitudes and perceptions toward marriage that are reflected in the current disparity in marital status among U.S. Blacks—48% of BIs are married compared to 28% of AAs (Pew Research Center, 2015).…”
mentioning
confidence: 99%